2014
DOI: 10.1111/adb.12200
|View full text |Cite
|
Sign up to set email alerts
|

Enkephalin is essential for the molecular and behavioral expression of cocaine sensitization

Abstract: Behavioral sensitization to cocaine is associated to neuroadaptations that contribute to addiction. Enkephalin is highly expressed in mesocorticolimbic areas associated with cocaine-induced sensitization; however, their influence on cocaine-dependent behavioral and neuronal plasticity has not been explained. In this study, we employed a knockout (KO) model to investigate the contribution of enkephalin in cocaine-induced behavioral sensitization. Wild-type (WT) and proenkephalin KO mice were treated with cocain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 58 publications
3
36
0
Order By: Relevance
“…after a long-term abstinence from the drug (12 days after last injection). Met-enkephalin immunoreactivity elevations induced by chronic cocaine is not dependent of cocaine challenge administration (7.5 mg/kg i.p., day 21), as this effect on met-enkephalin immunoreactivity was also observed after saline challenge injection ( 19 ).…”
Section: Activation Of the Enkephalin System By Psychostimulants In Tmentioning
confidence: 71%
See 4 more Smart Citations
“…after a long-term abstinence from the drug (12 days after last injection). Met-enkephalin immunoreactivity elevations induced by chronic cocaine is not dependent of cocaine challenge administration (7.5 mg/kg i.p., day 21), as this effect on met-enkephalin immunoreactivity was also observed after saline challenge injection ( 19 ).…”
Section: Activation Of the Enkephalin System By Psychostimulants In Tmentioning
confidence: 71%
“…Although several pharmacological and genetic approaches demonstrate a role of both MOPr and DOPr in psychostimulant-induced behavioral effects, the role of the endogenous opioid peptides in this process has not been fully examined. Previous studies from our lab have demonstrated a long-lasting increase in enkephalin levels within the mesocorticolimbic circuit after psychostimulant administration ( 18 , 19 ). Enkephalin has also been shown to positively modulate dopamine and glutamate neurotransmission within this circuit ( 20 – 25 ).…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations